Study on the Effect of Oil Supply on the Sound Field Characteristics of Full Ceramic Ball Bearings under Oil Lubrication - Jian Sun; Xin Fang; Jinmei Yao; Renyun Guan; Zhe Zhang; Guangxiang Zhang (Lubricants, 2023)
To study the full sound field distribution characteristics of full ceramic ball bearings, reduce the radiation noise of the bearings, and improve their service performance. In this paper, the sound field distribution characteristics of 6206 silicon nitride ceramic deep groove ball bearings are studied under different oil supplies. A mathematical model of the sound field distribution of full ceramic ball bearings under oil lubrication is established, and the validity of the model is verified by experimental data. The bearing cavity simulation model of the full ceramic ball bearing is established, and the influence of oil supply on the operation characteristics of the full ceramic ball bearing is studied. Through theoretical and experimental research, the circular distribution law of the noise signal of ceramic ball bearings under different oil supplies is revealed. It is found that there is an optimal fuel supply when the speed and load are constant. Under optimal oil supply lubrication conditions, the full ceramic ball bearing has the minimum radiation noise, and the bearing exhibits optimal lubrication state, vibration and temperature rise characteristics. The new contribution of this paper: with the increase in oil supply, the sound pressure level of radiation noise of full ceramic ball bearings decreases and then increases. The research results reveal the radiation noise mechanism of full ceramic ball bearings, which is of great significance for enriching its theory and method.